Quirky Quotes and Needles in the Haystack: Tracing Grammatical Change in Untagged Corpora - Muriel Norde (Linguistik Online, 2014)
This paper discusses pivotal theoretical and methodological problems of historical corpus linguistics. In two case studies from Swedish language history, the development of the epistemic adverb kanske and the group genitive respectively, it illustrates how the use of qualitative method in addition to corpus investigation can contribute to understanding grammatical change.